UPAYA MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS MELALUI FILM - Rian Sri Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the effectiveness of using English-language films as a medium to improve the speaking skills of first-year university students. The main issues raised were low self-confidence and lack of exposure to natural conversational contexts among Indonesian university students. Using descriptive qualitative methods, the study involved five university students who were asked to regularly watch English-language films for one semester. Data were collected through weekly observations, and in-depth interviews at the end of the semester. The results showed that the use of films had a positive impact on students' pronunciation confidence and expanded vocabulary. However, significant improvements in interaction were only seen in students who also practiced the language in everyday settings. The study concluded that films are an effective supplementary medium, but they must be combined with active practice and formal guidance to achieve optimal fluency.